VD_FINDINFO HC / 2014 / 231 vom 14. März 2014 - VD Tribunal cantonal (2014)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, ADMINISTRATION DES PREUVES | 176 al. 1 ch. 1 CC, 176 al. 1 ch. 3 CC